Premature Ovarian Failure and Epilepsy - Permana, Hendra; Rahmi, Afriyeni Sri; Muhammad, Syamel (Fakultas Kedokteran Universitas Andalas, 2021)
Premature ovarian failure (POF) or premature menopause refers to development of amenorrhoea due to cessation of ovarian function before the age of 40 years. The diagnosis is based on elevated FSH levels in menopausal range (usually above 40 IU/l) detected on at least two occasions a few weeks apart. The term â€œepilepsyâ€ defines a group of disorders characterized by an enduring predisposition of the brain to produce seizures. The hypothalamic-pituitary-ovarian axis regulation is affected by the abnormal neurophysiology of seizures, and the hypothalamic-pituitary-ovarian associated hormones are affected by medications used to treat seizures in women with epilepsy. Ictal and interictal discharges can disrupt the normal activity of brain structures, including the limbic system, amygdala, hypothalamus, and pituitary gland. Management of epilepsy in women requires not only knowledge of epilepsy, but also recognition of the various roles and priorities women have in their lives (education, career development, child rearing, the role as carer within the extended family), and attention to gender-specific issues and their impact on patientsâ€™ wellbeing throughout life.Keywords: premature ovarian failure (POF), epilepsy